Barriers to Employment Participation of Individuals With Disabilities: Addressing the Impact of Employer (Mis)Perception and Policy. (May 2018) - Baker, Paul M. A.; Linden, Maureen A.; LaForce, Salimah S.; Rutledge, Jennifer; Goughnour, Kenneth P.
Although progress has been made toward the objective of increased employment for people with disabilities, the 17.2% employment rate of people with disabilities stands in distressing contrast to the 65% rate of those without disabilities. This article summarizes the results of a comparative survey of representative academic literature and industry publications related to employer policies and practices that can affect workforce participation of individuals with disabilities. Emergent themes include variance in employer perspectives on hiring of individuals with disabilities, impact of perceived versus actual cost as a hiring barrier, and the perceived mismatch of education and/or skills to job qualifications among applicants with disabilities. These themes represent key areas to probe in subsequent research. The research objective is to identify focal points in the industry literature, representative of employer and industry (demand side) points of view that differ from those generally portrayed in the academic literature (more generally, supply side). Findings from a thematic analysis of industry publications can provide (1) evidenced based background to assist in crafting targeted policy to address employer awareness, (2) informed development of industry guidance on topics that may assist employers to achieve a more inclusive workplace, and (3) insights applicable to addressing barriers to broadening participation by technical, scientific, and engineering trained individuals with disabilities.